PENGARUH CORPORATE GOVERNANCE, KONEKSI POLITIK, DAN LEVERAGE TERHADAP PENGHINDARAN PAJAK - Lestari, Gusti Ayu Widya; Putri, I.G.A.M Asri Dwija (E-Jurnal Akuntansi, 2017)
Tax revenue is important  because it provides the largest contribution to the state revenue. Companies often take measures to reduce its tax burden. One of the actions  is tax avoidance. This study examined the effect of corporate governance, political connections, and  leverage  against tax evasion. Businesses will be observed is a company registered in the Indonesia Stock Exchange during 2011-2015. Companies that used to sample after deducting some of the criteria were 62 observations. Analysis of data using multiple linear regression. Variable tax evasion proxied by Cash ETR. The results showed that corporate governance, political connections, and leverage effect simultaneously against tax evasion. Corporate governance and leverage effect on tax evasion. Political connections has no effect on tax evasion.
Keywords: tax avoidance, corporate governance, leverage